The teaching clinic as a space for ethical, technical and civic training: the importance of supervised internship in psychology (Research, Society and Development, 2025)
This article aims to analyze the contribution of supervised internships in teaching clinics to the critical, ethical, and civic development of Psychology students. Based on a bibliographic and documentary review, the study articulates curricular guidelines, legal frameworks, and academic literature that consider teaching clinics as a privileged space for comprehensive training. The data analyzed demonstrate that supervised practice fosters the integration of theory and practice, enabling the development of applied knowledge that is sensitive to social demands and committed to transforming reality. Supervision, in this context, proves to be an essential pedagogical tool, guiding students in the critical analysis of clinical situations and in decision-making based on the principles of the Psychologist's Code of Professional Ethics. The study also identified structural challenges in the training process, such as the lack of methodological standardization across institutions, heterogeneity in the theoretical frameworks used, and gaps in integration with the public health system. Despite these obstacles, the teaching clinic reaffirms its centrality in the training of psychologists by combining technical education with ethical and political training. The analysis concludes that psychology training, when combined with a supervised internship in a teaching clinic, strengthens the profession's social commitment, developing ethical and political individuals capable of acting critically, autonomously, and responsibly in the face of complex human realities. The study therefore contributes to a deeper reflection on the training processes in psychology, pointing the way toward a higher education committed to social justice and democratic principles.